Correlation Between the Thyroid Imaging Reporting and Data System and Bethesda System of Cytology in Thyroid Nodule Evaluation - Omer Bahabara, Jamal; Salem Basabaa, Ahmed; Mohammed Bin Thalab, Abeer; Yeslam Baothman, Sameer; Khamis Alakbary, Mohammed; Salim Musiaan, Nabeel (Diyala Journal of Medicine, 2024)
Background: Accurate diagnosis of thyroid nodules is important for avoiding unnecessary surgeries and allowing timely treatment. Ultrasound and fine needle aspiration cytology (FNAC) are the most commonly used diagnostic procedures. Objective: To correlate ultrasonography with the FNAC report findings using the American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI-RADS) and the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) in differentiating malignant from benign thyroid nodules. Patients and Methods: A prospective study conducted from January 2021 to January 2024 assessed 103 cases of thyroid nodules who underwent ultrasound examination and fine needle aspiration. Ultrasonography findings were analyzed and correlated with FNA cytology reports based on ACR-TIRADS and BSRTC. Results: Patients were predominantly female, n = 87 (84.4%). Most of the patients were in the 31–40 year group (n = 55, 53.39%). Most of the patient nodules had TIRADS 3 (n = 59, 57.28%), followed by TIRADS 2 (n = 20, 18.44%). When comparing the ACR TI-RADS scoring system with the TBSRTC, the percentage of malignancy for TR1, 2, 3, 4, and 5 was 0, 0, 1.6, 80, and 89%, respectively. In our study, the overall sensitivity and specificity of the TIRADS score were 94.11% and 96.51%, respectively. PPV: 84.21%; NPV: 98.80%; and accuracy: 96.11%. In addition, there was a significant association between TIRADS and the Bethesda system of classification (P < 0.001). Conclusion: ACR-TIRADS scoring is highly sensitive and accurate for diagnosing thyroid malignant nodules. It is a sensitive tool and could be used alone to determine the nature of thyroid nodules.